Pengukuran Tingkat Kepentingan Masyarakat dalam penggunaan Shampo Viral Korea dengan Metode Kano Model - Robert Candra; Desrina Yusi Irawati (Universitas Katolik Darma Cendika, 2022)
Shampoo is a human need that is used to clean the scalp and hair. Shampoo is usually used every 2-3 days to keep hair clean and healthy. It contains proplene glycol; diethanolamine; triethanolamine; sodium lauryl sulfate; parabens; sodium chloride. However, there are still many people who do not understand the importance of shampoo and measuring their level of satisfaction with the product. By measuring the level of consumer satisfaction, product/service providers can make changes to their products/services so that they can affect them effectively in people's lives. This journal will discuss the level of public satisfaction with Korean viral shampoo. The level of community satisfaction can be demonstrated using the Kano Model research method. The survey will be conducted with a sample of 64 respondents who come from different backgrounds but understanding the performance of Korean viral shampoos. The resulting data will be implemented in the required variable table by providing functional and dysfunctional questions. The results of the data show that Korean viral shampoo does not require overhauling in terms of quality, performance or characteristics because the level of customer satisfaction cannot affect it.